166 Predictors of Incomplete Aneurysm Occlusion After Treatment with Pipeline Embolization Device: PREMIER Trial 1-year Analysis. (1st April 2022) - Monteiro, Andre; Kallmes, David; Lopes, Demetrius K.; Nelson, Peter K.; Hanel, Ricardo A.
Abstract : INTRODUCTION: Failure of treatment with Pipeline Embolization Device (PED) occurs in 16.1% to 24.6% of aneurysms. Studies investigating mechanisms behind PED failure are mostly retrospective series with conflicting findings. We performed an analysis of aneurysms that failed to achieve complete occlusion in the Prospective Study on Embolization of Intracranial Aneurysms with the Pipeline Device (PREMIER) trial. METHODS: PREMIER was a prospective, multicenter and single-arm interventional. Assessment images was done by independent core laboratory. We retrospectively analyzed patients who failed the primary efficacy endpoint. Aneurysms with incomplete occlusion (RR > 1) were further analyzed and compared to completely occluded aneurysms. RESULTS: Twenty-five (18.1%) aneurysms were incompletely occluded at 1-year. Twenty-two patients had RR-3 and 3 had RR-2. There was a median reduction of 0.9 mm (IQR 0.41-2.43) in maximum-diameter between pre-procedure and 1-year follow-up. Mean age of patients with incomplete occlusion was significantly higher than in those with complete occlusion (mean ±SD; 59.9 ± 10.4 vs 53.6 ± 11.2, P = 0.011). Smoking (P = 0.045) and C6 segment location (P = 0.005) were significantly associated with complete occlusion, while location at V4 (P = 0.01) and C7 (P = 0.007) segments and involvement of a side branch (<0.001) were significantly associated with incomplete occlusion. There was no difference in the rate of inadequate wall apposition between complete and incomplete occlusion groups (12% vs 12.4%, P = 1). In multivariable logistic regression, significant predictors of incomplete occlusion were non-smoker status (adjusted OR, 4.49; 95% CI, 1.11-18.09; p = 0.03), and side branch involvement (adjusted OR, 11.68; 95% CI, 3.84-35.50; P < 0.0001), while the C6 location had reduced odds of incomplete occlusion versus those at other segment locations (adjusted OR, 0.29; 95% CI, 0.10-0.84; p = 0.02). CONCLUSION: In the PREMIER cohort, non-smoking status and vessel branch involvement were the strongest predictors of incomplete occlusion at 1-year. Although the presence of side branches can lead to incomplete occlusion, we observed decrease in aneurysm size and stable remodeling. The efficacy of protecting against rupture remains to be confirmed in longer follow-up. The results from our prospective study is consistent with previous retrospective series and warrants considerations for technique adaptations to achieve higher occlusion rates.